2015
DOI: 10.1002/etc.2855
|View full text |Cite
|
Sign up to set email alerts
|

The influence of natural organic matter and aging on suspension stability in guideline toxicity testing of silver, zinc oxide, and titanium dioxide nanoparticles with Daphnia magna

Abstract: The present study investigated changes in suspension stability and ecotoxicity of engineered nanoparticles (ENPs) by addition of Suwannee River natural organic matter and aging of stock and test suspensions prior to testing. Acute toxicity tests of silver (Ag), zinc oxide (ZnO), and titanium dioxide (TiO2) ENPs with Daphnia magna were carried out following Organisation for Economic Co‐operation and Development test guidelines. Daphnia magna was found to be very sensitive to Ag ENPs (48‐h 50% effective concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 45 publications
2
48
1
2
Order By: Relevance
“…For detAgNP in the same medium, colloidal instability and increasing agglomerate size as well as relatively stable small aggregates of about 60 nm size have been reported (Baumann et al, 2014b;Cupi et al, 2015;unpublished data). In the present study, agglomerate sizes were constant, but a bit larger than reported for the stable dispersions.…”
Section: Discussionmentioning
confidence: 68%
“…For detAgNP in the same medium, colloidal instability and increasing agglomerate size as well as relatively stable small aggregates of about 60 nm size have been reported (Baumann et al, 2014b;Cupi et al, 2015;unpublished data). In the present study, agglomerate sizes were constant, but a bit larger than reported for the stable dispersions.…”
Section: Discussionmentioning
confidence: 68%
“…This led to a sludge-soil-ratio of 5t/ha which can be applied to agricultural used land according to the German Sewage Sludge Ordinance (AbfKlärV §6 Absatz 1 1992) within 3 years. Furthermore, the organic matter content or the texture of the test soil can have a strong influence on the toxic effect of AgNM (Collin et al 2014; Cupi et al 2015; Schlich and Hund-Rinke 2015). In the present experiment a sandy loam was used as test soil sieved ≤2 mm before the soil was filled into the lysimeters, whereas Colman et al (2013) used a mineral soil from a floodplain with a high clay content (26%) sieved to 10 mm before test start.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit for ecology applications, cell-based assay systems are less frequently used, current developments allow expanding their applications also in nano-ecotoxicology, 177,178 including for water organisms, such as fish 179 or Daphnia magna cell lines, 180 as well as for soil organisms, 181 including Enchytraeus crypticus models. However, although such comprehensive information is key for the subsequent interpretation and prediction of potential corona-mediated biological effects, these data have to be complemented by biological assay systems of varying complexity.…”
Section: The Power Of the Np-corona In In Silico Modellingmentioning
confidence: 99%